Prototype Model Bimbingan BTQ untuk Mahasiswa Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang - Abdul Rozaq; Kholisin; Masiran (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2023)
This study aims to describe and analyze a prototype model of Al-Qur'an reading and writing guidance for students of the Da'wah and Communication Faculty of UIN Walisongo Semarang. This research uses a qualitative method with a case study type. The object of his research is active Da'wah and Communication Faculty students. Data was collected through interviews, observation, and documentation. Data analysis techniques use interactive models consisting of data reduction, data presentation, and drawing conclusions. The results showed that there are many models of Al-Qur'an reading and writing guidance that exist, including guidance models by applying the Qira'ati method, the An-Nahdliyah method, the Al-Barqy method, the Iqra method, the Dirosa method, the Al-Barqy method, Baghdadi method, Yanbu'a method, and Ummi method. In the application of these methods to students of the Faculty of Da'wah and Communication, almost all methods were captured and able to be applied by students of the Faculty of Da'wah and Communication, it's just that there are still some methods that are foreign to students' ears and have some difficulties in their application. Based on the application of these methods to students of the Faculty of Da'wah and Communication, everything went smoothly. Students can be successful in reading and writing the Qur'an with regular and continuous conditions in learning. This proves that all methods are good on condition that they are done regularly and continuously.